Development of hearing impairment inventory for religious duties for Muslim adults: a preliminary study - Rahmat, Sarah; A Rahman, Shahirah; Tukiran, Nur Hanisah; Musa, Ramli; Othman, Nur Ain; Arafat Dzulkarnain, Ahmad Aidil (2021)
Objective: This study is a preliminary work to develop a Malay version questionnaire named ‘Inventori Persepsi bagi Muslim yang Memiliki Masalah Pendengaran (IPM3P)’ to assess the perception on Islamic understanding and practice among Muslim adults with hearing impairment. Methods: The scale development involved three phases: i) generation of domains based on the literature, ii) generation of sub-domains based on literature review and Islamic panel survey, and iii) generation of items. Results: Preliminary version of IPM3P consists of 59 items was produced, representing three domains: Obligation (18 items), Practice (21 items), and Difficulty (20 items), and seven sub-domains (‘Ibadah’, ‘Aqidah’, ‘Muamalat’, ‘Tasawwuf’, ‘Akhlak’,‘Da’wah’, and ‘Sirah’). Conclusion: The preliminary version of IPM3P needs to be psychometrically tested. This pioneering study may become an impetus towards more research pertaining to understanding the effect of hearing loss towards religious life in the future in Malaysia.